Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1093/emboj/16.9.2240
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory interactions in the recognition of endocytic sorting signals by AP-2 complexes

Abstract: 1995; Nesterov et al., 1995a;Ohno et al., 1995;Heilker et al., 1996). The α chain of the AP-2 heterotetramer can Many plasma membrane proteins destined for endobind clathrin (Goodman and Keen, 1995), synaptotagmin cytosis are concentrated into clathrin-coated pits (Zhang et al., 1994), Eps15 (Benmerah et al., 1995 Tebar through the recognition of a tyrosine-based motif ), Grb2 (Okabayashi et al., 1996 and small their cytosolic domains by an adaptor (AP-2) complex.phosphorylated molecules like inositol phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
186
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(198 citation statements)
references
References 80 publications
(200 reference statements)
9
186
0
3
Order By: Relevance
“…Previously, it was observed that PtdIns(3)P and, to a lesser extent, PtdIns(3,4)P 2 enhanced the binding of AP2 adaptors to peptides containing internalization signals. Clathrin binding enhanced the affinity of AP2 for internalization signals to a similar extent, but the effect of clathrin and PtdIns(3)P were not additive (286). However, when fluorescent proteins that bind PtdIns(3)P are expressed in cells, they label endosomes and not the plasma membrane (32,92,318), suggesting that there is little free PtdIns(3)P at the cell surface.…”
Section: Ptdins3kiic2␣mentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, it was observed that PtdIns(3)P and, to a lesser extent, PtdIns(3,4)P 2 enhanced the binding of AP2 adaptors to peptides containing internalization signals. Clathrin binding enhanced the affinity of AP2 for internalization signals to a similar extent, but the effect of clathrin and PtdIns(3)P were not additive (286). However, when fluorescent proteins that bind PtdIns(3)P are expressed in cells, they label endosomes and not the plasma membrane (32,92,318), suggesting that there is little free PtdIns(3)P at the cell surface.…”
Section: Ptdins3kiic2␣mentioning
confidence: 94%
“…Mutation of the PIP binding site on the AP2␣ subunit inhibits membrane binding, and mutation of the binding site on the AP2 subunit prevents binding to cargo, demonstrating the importance of the interaction with PIPs (111,291). AP2 can bind multiple PIPs, and in vitro those with D-3 phosphate increase the affinity of AP2 complexes for peptides that have internalization signals (286). This may be relevant to the observations that PtdIns3KIIC2␣ localizes in clathrin-coated pits (112) and that PtdIns(3,4,5)P 3 is important for recruitment of AP2 to activated ␤-adrenergic receptors (248).…”
Section: A Ptdins(45)p 2 At the Plasma Membranementioning
confidence: 99%
“…The heterotetramers of AP2 and AP1 have at least two distinct states-a closed or "locked" state and one or more open states (Rapoport et al 1997;Collins et al 2002;Jackson et al 2010). In the closed state, two well-studied cargo-binding sites are buried (Fig.…”
Section: Heterotetrameric Clathrin Adaptorsmentioning
confidence: 99%
“…A clathrin box in the hinge domain and an additional domain near the ear domain of the ß2-subunit facilitates direct binding to clathrin (Ahle and Ungewickell, 1989;Kirchhausen et al, 1989;Mousavi et al, 2004) and facilitates clathrin assembly. The ß2-subunit may also be involved in cargo recognition (Rapoport et al, 1998). Cargo is recruited through interactions between sorting motifs in protein cargo and the AP-2 complex.…”
Section: Ap-2mentioning
confidence: 99%